MODELLING OF THE SYSTEM OF THE DEVELOPMENT OF FUNCTIONAL MATHEMATICAL LITERACY IN STUDENTS HAVING MODERATE SPECIAL EDUCATIONAL NEEDS IN PRACTICE: PEDAGOGUES’ APPROACH - Baranauskienė, Ingrida; Tomėnienė, Laima (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with the strategies used in of mathematical education, while creating the methodology of the development of mathematical literacy in senior class students of mainstream schools having moderate special educational needs oriented towards the development of functional students’ abilities in practice. 20 pedagogues (teachers of mathematics and special pedagogues) developing mathematical abilities of 30 students having moderate special educational needs in the 8th forms of mainstream schools participated in the action research. As it is shown in the scientific literature, the performed action research has been analyzed: its peculiarities and strategies of application in creating the methodology of the development of functional mathematical literacy in students with moderate special educational needs in the 8th form of mainstream school have been revealed